2010
DOI: 10.1007/s11240-010-9716-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokinins, carbohydrates and amino acids on induction and maturation of somatic embryos in kodo millet (Paspalum scorbiculatum Linn.)

Abstract: The effects of cytokinins, carbohydrates and amino acids were studied on maturation and regeneration of embryogenic callus (EC) in kodo millet (Paspalum scorbiculatum Linn.) using a two-step culture procedure. The highest percentage (87.6%) of EC induction was obtained in the induction medium containing Murashige and Skoog (MS) basal salts supplemented with 9.0 lM 2,4-dichlorophenoxy acetic acid and 2.25 lM kinetin. This EC was subcultured in the maturation medium for somatic embryo (SE) maturation and plantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 48 publications
(39 reference statements)
4
8
0
Order By: Relevance
“…The successful use of shoot apical meristems explants in this study implies that they are a better choice for plant regeneration in cereals when compared to other explants. This study therefore confirms previous reports by Ramakrishnan et al (2014) and Ceasar and Ignacimuthu (2010). Mature seeds derived explants are better source material for tissue culture research than others because of the availability of seeds, ease of storage of seeds, and homogeneity quality of the explants (Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…The successful use of shoot apical meristems explants in this study implies that they are a better choice for plant regeneration in cereals when compared to other explants. This study therefore confirms previous reports by Ramakrishnan et al (2014) and Ceasar and Ignacimuthu (2010). Mature seeds derived explants are better source material for tissue culture research than others because of the availability of seeds, ease of storage of seeds, and homogeneity quality of the explants (Yang et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Ashok Kumar et al (2000) also reported somatic embryos development from leaf explants on MS medium containing 2, 4-D in combination with BAP or Kin. Similar findings were also observed in case of kodo millet (Ceasar and Ignacimuthu 2010) and finger millet (Ceasar and Ignacimuthu 2008). Addition of BA in combination with 2,4-D to callus induction medium stimulated somatic embryogenesis and percentage of shoot-forming calli in Kentucky bluegrass (Poa pratensis L.) caryopsis culture (van der Valk et al 1995).…”
Section: Discussionsupporting
confidence: 83%
“…The induction of somatic embryogenesis has been achieved in several plant species by altering concentration and combination of auxins and cytokinins (Adda et al 1994;Ashok Kumar et al 2000;Ceasar and Ignacimuthu 2010), age of the cultures (Andrýskova et al 2009), osmotic stresses (Groll et al 2002;Zavattieri et al 2010), physiochemical factors (Hofmann et al 2004) and nitrogen sources (Sen et al 2002;Awal et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the ROS generated by inductive stresses can modify the effectiveness of microspore embryogenesis, influencing both cell viability and cell metabolism ( _ Zur et al 2009( _ Zur et al , 2014 and proline can function as non-enzymatic antioxidant by scavenging the ROS produced by inductive stresses and reestablish redox homeostasis (Szabados and Savouré 2009). The enhancing effect of proline on somatic embryogenesis induction has also been observed in several species (Ceasar and Ignacimuthu 2010;Nhu et al 2012). Patnaik et al (2005) applied polyethylene glycol (PEG-8000), mannitol and air drying treatment for somatic embryogenesis induction in T.aestivem L. Surprisingly, they observed twofold to fivefold increase in the endogenous level of proline content in embryogenic explants compared with non-embryogenic explants (untreated cultures).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the effects of three different amino acids i.e. proline, serine and glutamine on somatic embryogenesis in P. scorbiculatum L., Ceasar and Ignacimuthu (2010) noted that the MS medium containing 25 mg l -1 proline was superior to that containing serine and glutamine or untreated cultures in the term of somatic embryo formation and maturation. In addition, significant increase in the number of somatic embryos produced from in vitro cultured main root transverse thin cell layers of Panax vietnamensis was observed when 300 mg l -1 proline was exogenously applied to the induction medium (Nhu et al 2012).…”
Section: Discussionmentioning
confidence: 99%